Effects of balance training in addition to auxiliary activity on balance function of patients with stroke at high risk for falls - Tan, Huiqun; Gong, Zhaohui; Xing, Sisi; Cao, Lanhua; Liu, Huan; Xu, Lijun (Frontiers in Neurology, 2023)
Objective: The aim of this study was to investigate the effect of balance training in addition to auxiliary activity on the balance function of stroke patients at high risk for falls. Methods: A total of 112 Stroke patients at high risks for falls in our hospital from inception to January 2020 to December 2020 were selected as the research objects who were equally divided into control group and study group according to the random number table method. The patients in control group were intervened with auxiliary activity, and the patients in study group received additional balance training to auxiliary activity. The balance function, lower extremity motor function, fall risk, walking ability and other indicators were compared between the two groups of patients before and after treatment. The hospitalization time and the frequency of falls 3 months after discharge were also compared between the two groups. Results: Before treatment, there was no significant difference in balance function, lower extremity motor function, fall risk and walking ability scores between the two groups (P>0.05). Three months after treatment, the balance function, lower extremity motor function and walking ability scores of the study group were significantly higher than those of the control group, with the fall risk score significantly lower than that of the control group (P<0.05). Evidently lower hospitalization time and the frequency of falls in the 3-month follow-up of study group were observed than those in control group (P<0.05). However, there was no significant difference in the frequency of falls between the two groups during hospitalization (P>0.05). Conclusions: Our results indeed revealed that balance training in addition to auxiliary activity elicited beneficial outcomes in term of effectively improving the balance function and walking ability of stroke patients at high risk of falling, which may have the potential for wide clinical application.